EarthArXiv (Eartharxiv.org, 2017)
"EarthArXiv is a preprint server devoted to open scholarly communication. EarthArXiv publishes articles from all subdomains of Earth Science and related domains of planetary science. The EarthArXiv platform assigns each submission a Digital Object Identifier (DOI), therefore assigning provenance and making it citable in other scholarly works. EarthArXiv does not evaluate the scientific quality of submissions. Instead, EarthArXiv serves as a volunteer community-driven platform for free hosting and rapid dissemination of scientific results."